Correlation of cell apoptosis index and hematology profile in children with acute myeloblastic leukemia with chemotherapy induction - Arief Rahman; Susanto Nugroho; Sony Wicaksono (Medical Faculty of Brawijaya University, Indonesia, 2022)
Background: Acute myeloblastic leukemia (AML) is one of the most prevalent pediatric neoplasms, with a poor prognosis and high risk of relapse. Response to induction of chemotherapy and complication occurrence are crucial in the AML patient's outcome. Chemotherapy can induce apoptosis in a cancer cell and the blood cell as a side effect that can cause severe complications. This study aims to evaluate the cell apoptosis index and its correlation with hematologic profile (hemoglobin, leucocyte, thrombocyte, absolute neutrophile count/ANC) between induction chemotherapy administration. Methods: Observational study was performed on children with AML who will undergo induction chemotherapy. The cell apoptosis index and the hematologic profile were evaluated before and after induction chemotherapy. The data was then analyzed to compare the cell apoptosis index and its correlation with the hematologic profile. Result: The mean age of the subjects was 13.6 years old, similar to previous epidemiologic studies, which showed the main incidence at 15 years old. There was a significant increase in cell apoptosis index (p=0.014) and a significant decrease in hemoglobin level (p=0.031) and ANC (p=0.05). The cell apoptosis index had a significantly strong negative correlation with all hematologic profiles. Conclusion: Cell apoptosis index increased after induction chemotherapy in pediatric AML and correlated with the hematologic profile.